Gall wasp (Cynipoidea: Cynipidae and Diplolepididae) fauna of the Eastern Black Sea Region (Türkiye) - Tataroğlu, Musa; Katilmiş, Yusuf (Zootaxa, 2024)
In the period between October 2017 and September 2019, field studies were conducted with the aim of elucidating the gall wasp (Hymenoptera: Cynipidae and Diplolepididae) fauna of the Eastern Black Sea Region (Northeastern Türkiye). Gall samples were collected from 695 different localities within the research area, comprising a total of seven provinces (Artvin, Bayburt, Giresun, Gümüşhane, Ordu, Rize and Trabzon). As a result of these investigations, a total of 90 species belonging to 18 genera were recorded. Three of these species (Synergus consobrinus Giraud in Houard, 1911; S. reinhardi Mayr, 1872; S. ruficornis Hartig, 1840) represent new records for the inquiline (Synergini) fauna of Türkiye. The host plants, distributions, and distribution maps for all of the species recorded from the Eastern Black Sea Region are provided.